Analisis Perbedaan Kadar Vitamin C Buah Naga Merah (Hylocereus polyrhizus) Dan Buah Naga Putih (Hylocereus undatus) Yang Tumbuh Di Desa Kolono Kabupaten Morowali Provinsi Sulawesi Tengah - Risnayanti, Risnayanti; Sabang, Sri Mulyani; Ratman, Ratman (Universitas Tadulako, 2015)
This study aims to determine the differences of vitamin C levels contained in the red dragon andwhite dragon fruits. The flesh and the skin of the dragon fruits were used as the samples and the fruitswere taken from Kolono Village, Morowali. Analysis of vitamin C levels in the samples was done byiodine titration method using starch solution as an indicator. The results showed that vitamin C levelsin the skin of red dragon fruit was 4.04 mg/100 g, while in the flesh was 5.28 mg/100 g. Levels ofvitamin C in the skin of white dragon fruit was 7.56 mg/100 g, while in the flesh was 7.92 mg/100g. The data indicate that vitamin C levels in the flesh and the skin of white dragon were higher thanvitamin C levels in the flesh and the skin of red dragon fruit. It can be seen that both of fruits havedifferent vitamin C levels.